Negative impact of the first COVID-19 lockdown upon health-related behaviours and psychological wellbeing in people living with severe and complex obesity in the UK. (April 2021) - Brown, Adrian; Flint, Stuart W.; Kalea, Anastasia Z.; O'Kane, Mary; Williams, Simon; Batterham, Rachel L.
Abstract: Background: Coronavirus disease 2019 (COVID-19) has led to unprecedented changes in the way we live, particularly for people at higher risk of severe illness from COVID-19. People with pre-existing health conditions have been markedly impacted and, in some instances, left unsupported due to reduced provision of routine healthcare services. People living with obesity (PLWO) are identified as at higher risk of severe illness from COVID-19 infection. Currently, there is a paucity of evidence about the impact of the first COVID-19 lockdown on PLWO, including those accessing weight management and bariatric surgery services (WMS). Methods: 543 adults (16–80 years) with obesity (BMI ≥ 30 kg/m 2 ) were recruited between 14th May and 9th July 2020 through social media advertisements, professional and patient obesity organisations and WMS. Participants completed an online survey regarding the impact of the first COVID-19 lockdown upon, mental health, well-being, health-related behaviours, risk mitigating behaviours, access to WMS and weight stigma. Findings: During the first COVID-19 lockdown, the majority of PLWO reported deterioration of their mental health and health-related behaviours such as diet, physical activity (PA) and sleep. With 55% reporting an unhealthier diet, 61% reduced PA and 80% worsening of their sleep. Higher depression and lower wellbeing scores were found to associate with the greatest adverse impact upon health-related behaviours. PLWO who were attending WMS prior to the first lockdown reported a greater deterioration of their diet, with nearly 50% reporting worsening of their diet and PA worsening compared to PLWO who were not attending WMS. Most participants took two or more risk mitigating actions (73%). PLWO attending WMS reported reduced access (44%) with insufficient information (49%) from their clinical service providers. The majority of participants reported no change in perceived weight stigma. Interpretation: This study shows the detrimental impact of the first COVID-19 lockdown on PLWO in relation to health-related behaviours, mental health and access to WMS. Our findings show that PLWO with poor mental health and those attending WMS were most adversely impacted and highlights the need for greater mental health support and continued provision of support from WMS for PLWO during future lockdowns. Funding: This research was funded through National Institute for Health Research University College London Hospitals Biomedical Research Centre funding.